Critical theory since Plato - Adams, Hazard, 1926- (Harcourt Brace Jovanovich, 1971)
Critical theory since Plato is a chronologically-arranged anthology that presents a broad survey of the history and development of literary criticism and theory in Western culture. Written by two well-known scholars in the field of literary study, this well-respected text puts an emphasis on the individual contributors to the development of literary criticism, from Plato and Aristotle to the present.